Contract documents for supply, installation, testing and commissioning of 5 nos. 1500 kva and 1 no.500 kva diesel generator for 13 storied Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Cross World Power Ltd. to supply, installation, testing and commissioning of 5 Nos. 1500 KVA and 1 No. 500 KVA diesel generator for 13 storied Brac University new campus building.